The Application of Project-Based Learning in Enhancing Student Creativity and Collaboration in Physical Education Subjects - Heppy Hein Wainggai; Zainal Widyanto; Ewendi W. Mangolo; Rif’iy Qomarrullah (Universitas Negeri Semarang, 2025)
This study aims to examine the implementation of Project-Based Learning (PjBL) in enhancing student creativity and collaboration in Physical Education at State Junior High School 7 Jayapura. In the 21st century, conventional learning methods frequently prove to be ineffective in promoting active engagement and collaboration among students. This research employs a classroom action research method conducted over two learning cycles, involving 32 students from grade VIII. Data collection was carried out using observation sheets, student reflection journals, and performance-based assessments. The research findings indicate a significant improvement in students' creative thinking abilities, especially in designing and executing physical activities in innovative ways, as well as in collaborative skills such as idea sharing, conflict resolution, and group responsibility. The implementation of context-based project tasks, the provision of guided autonomy, and reflective discussions contribute to the creation of a more meaningful and engaging learning environment. These findings confirm that the PjBL model not only promotes the development of core competencies such as creativity and collaboration but also aligns with the goals of Physical Education in encouraging active participation and the holistic growth of students.